Experimental Study on Frost-Heaving Force Development of Tibetan Clay Subjected to One-Directional Freezing in an Open System - Pengfei He; Meng Xiong; Yanhu Mu; Jianhua Dong; Xinlei Na (Advances in Civil Engineering)
Frost heave of soils involves complex coupled interactions among moisture, heat, and stress, which can cause serious damage to cold regions engineering. In this paper, a series of one-directional freezing experiments were implemented for the Tibetan clay with rigid restraint in an open system. The varying characteristics of the temperature, frost-heaving force, and water replenishment during the freezing process were analyzed under different freezing temperatures (−5, −7, and − 9°C), dry densities (1.65, 1.7, and 1.75 g cm−3), and initial moisture contents (11, 14, and 17%) of the soil samples. It was concluded that the freezing of soil samples mainly occurred within 10–25 hours from the beginning of the experiment; hereafter, the soil temperatures tended to be stable. The development of frost-heaving force could be divided into three stages as slow increase, quick increase, and relative stable stages. Low freezing temperature, large dry density, and high moisture content were all the contributors to the frost-heaving process of the soil, which could increase the freezing depth, magnitude of the frost-heaving force, and amount of water replenishment. The variations in water replenishment from the open system corresponded to the three stages of the frost-heaving force but had time lags. The moisture contents at different layers of soil samples were measured after the freezing experiment. The results showed that the freeze part of soil samples experienced a significant wetting, while the unfrozen part experienced drying during the experiment. The degrees of wetting and drying were related to the freezing temperature, dry density, and initial moisture content of the soil samples. The experiment results could provide data support for theoretical study on moisture, heat, and stress coupling in freezing soil.